The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 15th ACM / IEEE International Symposium on Empirical Software Engineering and Measurement (ESEM) 2021
DOI: 10.1145/3475716.3475781
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Rule-Based and Learning-Based Approaches for Static Application Security Testing

Abstract: Background: Static Application Security Testing (SAST) tools purport to assist developers in detecting security issues in source code. These tools typically use rule-based approaches to scan source code for security vulnerabilities. However, due to the significant shortcomings of these tools (i.e., high false positive rates), learning-based approaches for Software Vulnerability Prediction (SVP) are becoming a popular approach. Aims: Despite the similar objectives of these two approaches, their comparative valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 61 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…Language consideration could also be potentially strengthened in several research areas. For instance, vulnerability prediction models often do not consider the characteristics or features of the languages that they target (Yang et al 2017;Croft et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Language consideration could also be potentially strengthened in several research areas. For instance, vulnerability prediction models often do not consider the characteristics or features of the languages that they target (Yang et al 2017;Croft et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we computed the Matthews Correlation Coefficient (MCC) [70], which is a single-value classification metric that is more interpretable and robust to changes in the prediction goal [71] because it summarizes the results of all four quadrants of a confusion matrix, i.e., true positive, false negative, true negative, and false positive [72]. The MCC metric is calculated as MCC =…”
Section: Performance Metricsmentioning
confidence: 99%
“…Other studies, such as [20], focus on SAST tools for detecting vulnerabilities and find that the true positive and false positive rates vary widely across tools and across different types of vulnerabilities. Croft et al [21] compares open-source, rule-based SAST tools with learning-based software vulnerability prediction models for C/C++ software systems. Croft et al [21] concluded that although learning-based approaches had better precision, both learning-based and SAST tools approaches should be used independently.…”
Section: Comparing Static Application Security Testing (Sast) and Dyn...mentioning
confidence: 99%